Evolutionary conserved microRNAs are ubiquitously expressed compared to tick-specific miRNAs in the cattle tick Rhipicephalus (Boophilus) microplus - Barrero, R.; Keeble-Gagnère, G.; Zhang, B.; Moolhuijzen, Paula; Ikeo, K.; Tateno, Y.; Gojobori, T.; Guerrero, F.; Lew-Tabor, A.; Bellgard, M. (2011)
Background: MicroRNAs (miRNAs) are small non-coding RNAs that act as regulators of gene expression in eukaryotes modulating a large diversity of biological processes. The discovery of miRNAs has provided new opportunities to understand the biology of a number of species. The cattle tick, Rhipicephalus (Boophilus) microplus, causes significant economic losses in cattle production worldwide and this drives us to further understand their biology so that effective control measures can be developed. To be able to provide new insights into the biology of cattle ticks and to expand the repertoire of tick miRNAs we utilized Illumina technology to sequence the small RNA transcriptomes derived from various life stages and selected organs of R. microplus.Results: To discover and profile cattle tick miRNAs we employed two complementary approaches, one aiming to find evolutionary conserved miRNAs and another focused on the discovery of novel cattle-tick specific miRNAs. We found 51 evolutionary conserved R. microplus miRNA loci, with 36 of these previously found in the tick Ixodes scapularis. The majority of the R. microplus miRNAs are perfectly conserved throughout evolution with 11, 5 and 15 of these conserved since the Nephrozoan (640 MYA), Protostomian (620MYA) and Arthropoda (540 MYA) ancestor, respectively. We then employed a de novo computational screening for novel tick miRNAs using the draft genome of I. scapularis and genomic contigs of R. microplus as templates. This identified 36 novel R. microplus miRNA loci of which 12 were conserved in I. scapularis. Overall we found 87 R. microplus miRNA loci, of these 15 showed the expression of both miRNA and miRNA* sequences. R. microplus miRNAs showed a variety of expression profiles, with the evolutionary-conserved miRNAs mainly expressed in all life stages at various levels, while the expression of novel tick-specific miRNAs was mostly limited to particular life stages and/or tick organs.Conclusions: Anciently acquired miRNAs in the R. microplus lineage not only tend to accumulate the least amount of nucleotide substitutions as compared to those recently acquired miRNAs, but also show ubiquitous expression profiles through out tick life stages and organs contrasting with the restricted expression profiles of novel tick-specific miRNAs. © 2011 Barrero et al; licensee BioMed Central Ltd.